Rectal artemether versus intravenous quinine for the treatment of cerebral malaria in children in Uganda: randomised clinical trial - Aceng, Jane Ruth (BMJ Publishing Group Ltd., 2005)
Objective To compare the efficacy and safety of rectal artemether with intravenous quinine in the treatment of cerebral malaria in children. Design Randomised, single blind, clinical trial. Setting Acute care unit at Mulago Hospital, Uganda's national referral and teaching hospital in Kampala. Participants 103 children aged 6 months to 5 years with cerebral malaria. Intervention Patients were randomised to either intravenous quinine or rectal artemether for seven days. Main outcome measures Time to clearance of parasites and fever; time to regaining consciousness, starting oral intake, and sitting unaided; and adverse effects. Results The difference in parasitological and clinical outcomes between rectal artemether and intravenous quinine did not reach significance (parasite clearance time 54.2 (SD 33.6) hours v 55.0 (SD 24.3) hours, P = 0.90; fever clearance time 33.2 (SD 21.9) hours v 24.1(SD 18.9 hours, P = 0.08; time to regaining consciousness 30.1 (SD 24.1) hours v 22.67 (SD 18.5) hours, P = 0.10; time to starting oral intake 37.9 (SD 27.0) hours v 30.3 (SD 21.1) hours, P = 0.14). Mortality was higher in the quinine group than in the artemether group (10/52 v 6/51; relative risk 1.29, 95% confidence interval 0.84 to 2.01). No serious immediate adverse effects occurred. Conclusion Rectal artemether is effective and well tolerated and could be used as treatment for cerebral malaria.